Necessidades formativas de professores iniciantes que ensinam Matemática na rede municipal de Boa Vista-RR - Santos, Edlauva Oliveira dos (2018)
This research aimed to analyze the formative needs of beginners teachers who teach mathematics in the early years of Elementary School and how they attend in the continuous training developed by Boa Vista municipal school system, drawn from the question: what the formative needs of teachers beginners who teach mathematics in the early years of Elementary School and how they attend in the continuous training developed by Boa Vista-RR municipal school system? In the theoretical framework, we discuss the concepts: continuous teacher training, critical-reflexive teacher, formative needs, beginners teachers, teaching knowledge and mathematics teaching in the early years of Elementary School. In order to carry out the research, of a qualitative nature, we organized two moments: the first, of a more exploratory nature, occurred in the second half of 2016 and included the documents analysis that helped to know and understand the proposals of continuous training for mathematics teachers in the early years of Elementary School, the holding of a collective interview with the trainers of the Mathematics Education area of the municipal school system and the application of a questionnaire with 62 beginners teachers of the same scholl system; in the second moment, we deepened the study with the non-participant observation of the continuous training activities developed by the Municipal Education Department in the Mathematics Education área and the conduct of a partially structured interview with six beginners teachers who worked in the same school and participated in the first phase of the field study. The data analysis was performed according to the procedures of content analysis, having the theme as logging a unit. The results indicated that the teachers' needs are plural and exceed the training dimension, including the conditions for the continuous training activities themselves to take place. Such needs appear in different ways in the meetings, but are silenced by the lightened way they occur and by the focus on the instructions of the apostille system acquired by the municipal school system, which not only defines the teaching process in schools, but also the content, methodology, pace and mode of teachers participation. We also verified that there is no training program aimed to the needs of the beginners teachers, which corroborates that they adopt the teaching proposal of the apostille system as the main way of teaching, even knowing that it does not meet all the needs of the students, at the same time in which this causes frustration and disenchantment with the career.